Price, Marketing Communications and E-commerce Services on Consumer Purchase Intention in Online Shopping - Ummah, Roviqotul; Oetarjo, Mas (Indonesian Journal of Cultural and Community Development, 2024)
General Background: The rise of technology and internet use has significantly influenced shopping behaviors in Indonesia, particularly with the growth of online shopping. Specific Background: Factors such as price, marketing communication, and e-commerce services are essential in shaping consumer purchasing decisions in this digital space. Knowledge Gap: Limited research has examined the combined impact of these variables on online purchase intentions. Aims: This study investigates the effects of price, marketing communication, and e-commerce services on consumer purchasing intentions. Results: Using a quantitative approach with 96 respondents, the analysis reveals that all independent variables significantly influence consumer purchase intentions in online shopping. Novelty: This research integrates multiple influencing factors into a single study, emphasizing their collective impact. Implications: Findings indicate that e-commerce platforms should focus on competitive pricing, effective marketing strategies, and quality services to enhance consumer purchase intentions, contributing to a thriving online retail environment. Highlights: Significant Influence: Price, marketing communication, and e-commerce services collectively impact consumer purchasing decisions in online shopping. Research Gap: This study fills the void by examining the combined effects of multiple factors on purchase intentions. Strategic Implications: E-commerce platforms should prioritize competitive pricing and effective marketing strategies to boost consumer engagement and sales. Keywords: Price, Marketing Communication, E-Commerce Services, Consumer Purchase Intention, Online Shopping